Evaluation of Antifeedant Activity in Methanol Extracts of Zingiberaceae Species Against Epilachna sparsa - Purnama, Agnia; Nurdin, Nurdin; Ratna, Ratna; Farida, Mutia (Universitas Syiah Kuala, 2024)
Cellulosenanofibrils (CNF) is a new generation material that has high performance, good physics and medical properties and is a renewable material that has been developed from various sources using the acid hydrolysis method. CNF synthesis is generally obtained from logs that have a high amount of cellulose fiber. Cellulose nanofibrils (CNF) from arabica coffee skins have great potential to be developed as raw materials for medicines, which function as wound healing agents, surgical sutures, diet medicines, and skin softeners. CNF is produced from Arabica coffee skin through delignification, namely the removal of lignin and hemicellulose by extraction with alkali until -cellulose is obtained, then CNF is synthesized through hydrolysis using dilute acid. From the coffee skin extraction results, a high cellulose yield was obtained, reaching above 24.30% and crystallinity reaching 79.60%. Hydrolysis by 10%, 12% and 15% HCl with a reaction time of 2 hours, the respective crystallinity was 80.66; 79.06; and 77.69%.